2011
DOI: 10.1152/ajpregu.00793.2009
|View full text |Cite
|
Sign up to set email alerts
|

Electrostimulation during hindlimb unloading modulates PI3K-AKT downstream targets without preventing soleus atrophy and restores slow phenotype through ERK

Abstract: Our aim was to analyze the role of phosphatidylinositol 3-kinase (PI3K)-AKT and MAPK signaling pathways in the regulation of muscle mass and slow-to-fast phenotype transition during hindlimb unloading (HU). For that purpose, we studied, in rat slow soleus and fast extensor digitorum longus muscles, the time course of anabolic PI3K-AKT-mammalian target of rapamycin, catabolic PI3K-AKT-forkhead box O (FOXO), and MAPK signaling pathway activation after 7, 14, and 28 days of HU. Moreover, we performed chronic low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
54
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 45 publications
10
54
1
Order By: Relevance
“…It is well established, that proteinkinase mTORC1 is involved in the regulation of mRNA translation by phosphorylation of its downstream targets p70s6k and 4E-BP1 [11]. Surprisingly, we observed an increase in p70s6k phosphorylation after 1-and 3-day HS, although previously it had been shown a significant downregulation of p70s6k phosphorylation during longer periods of HS [19][20][21][22]. There is a growing body of evidence suggesting that mTOR-mediated p70s6k phosphorylation is not essential to sustain the normal maintenance of global protein synthesis.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…It is well established, that proteinkinase mTORC1 is involved in the regulation of mRNA translation by phosphorylation of its downstream targets p70s6k and 4E-BP1 [11]. Surprisingly, we observed an increase in p70s6k phosphorylation after 1-and 3-day HS, although previously it had been shown a significant downregulation of p70s6k phosphorylation during longer periods of HS [19][20][21][22]. There is a growing body of evidence suggesting that mTOR-mediated p70s6k phosphorylation is not essential to sustain the normal maintenance of global protein synthesis.…”
Section: Discussioncontrasting
confidence: 86%
“…For example, it has been shown that 14-day HS induces a significant reduction in phosphorylated AKT (Ser473) [19,20], p70s6k (Thr389) [19][20][21] and 4E-BP1 [19] in rat soleus muscle. At the same time, some authors did not find an increase in phosphorylated p70s6k (Thr389) in soleus after 10 days of mechanical unloading [22].…”
Section: Introductionmentioning
confidence: 99%
“…Among these pathways, the mitogen-activated protein kinases (MAPK-ERK1/2) are molecules typically involved in transduction of proliferative signals from extracellular origin. The family of serine/threonine kinases to which ERK belong, can be activated by a large variety of chemical [47] and physical stimuli [54,55,56]. ERK1 and ERK2 are fully activated through phosphorylation by MEKs (MAPK/ERK kinases).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, skeletal muscle exhibits alteration in PI3K/Akt/mTORC1 axis during immobilization [75,76,[80][81][82]. This phenomenon, called anabolic resistance, emphasizes the reduced response to anabolic stimuli [80,82].…”
Section: Cellular Mechanisms Involved In Immobilization-induced Skelementioning
confidence: 99%